Mathematics interest, self-esteem and mathematics achievement among physical module students at IIUM’s Foundation Studies / Juhaidah Hairom … [et al.] - Hairom, Juhaidah; Hisham, Balqis; Md Saad, Norlaili; Hassan, Suraya; Mohamad Hanafi, Nurfatihah; Mat Nawi, Mohd Nazim (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Interest is a significant factor that stimulates learning. Therefore, a student’s passion for mathematics is important for inspiring them to do well in any mathematics subject. Self-esteem is an attitude toward oneself. It is another crucial factor for a successful journey in seeking knowledge. This study investigates the interrelationship between gender differences in mathematics interest, self-esteem, and mathematics achievement among the Physical module students. The sampling technique used was purposive sampling. A sample of 238 Physical module students who are taking Mathematics II (MAT0124) in the Centre for Foundation Studies, International Islamic University Malaysia, session 20222023 was taken from them. The instrument used was Academic Interest Scale for Adolescents (AISA) to measure mathematics interest while the Rosenberg Self-Esteem Scale, which measures self-esteem. According to the findings, there was a significant difference between male and female students’ mathematics interest. On the other side, the self-esteem between male and female students revealed similarities which meant no significant difference. Correlation coefficient analysis revealed a significant correlation between mathematics interest and self-esteem among students. Further analysis showed that among different genders, there was a positive relationship between mathematics interest and their achievement. Moreover, there was a direct relationship between students’ self-esteem and their achievement. For future study, we can apply gamification technique during the next level of mathematics subject and study how the game will influence their interest in mathematics, self-esteem and their achievement.